Pengaruh Peer Acceptance Terhadap Kepercayaan Diri Siswa Pada Pembelajaran Bahasa Indonesia Kelas V Sekolah Dasar - Ainun Dwi Putri; St Nur Aisyah Ganis; Nadira; Muh. Aidil Fitrah Ripai; Muhammad Faisal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Education is a crucial process in shaping students' academic, social, and emotional development. At the elementary school level, students are not only required to understand the learning material but also to develop self-confidence in interacting, expressing opinions, and actively participating in classroom activities. Self-confidence is a crucial factor supporting student success in the learning process, particularly in Indonesian language learning, which requires the ability to speak, discuss, read, and express ideas directly. One factor influencing student self-confidence is peer acceptance. Students who are well-accepted by their peers tend to feel valued, comfortable, and more confident in participating in the learning process. Conversely, students who lack peer acceptance often feel shy, afraid, and less active in classroom learning activities. This article aims to determine the effect of peer acceptance on student self-confidence in fifth-grade elementary school Indonesian language learning. This study used a quantitative approach with a correlational approach. Data were collected by distributing questionnaires to students to measure their levels of peer acceptance and self-confidence. The data were analyzed using descriptive statistics and simple linear regression. The results showed that peer acceptance had a positive and significant effect on student self-confidence. The higher the level of peer acceptance, the greater the student's confidence in learning Indonesian. Therefore, a positive social environment needs to be developed to support the development of student self-confidence at school.